Research Collaboration and Global Migration - Halevi, Gali; Moed, Henk (International Higher Education, 2013)
This article presents two bibliometric techniques for the study of international scientific migration and international collaboration. The first is based on tracking of an author's career in terms of the institutions from which he or she has published their research articles, and the second on co-authorship relations between researchers active in different countries. To illustrate this analysis, we present results of 17 selected countries.